Approaches to open source 3-D printable probe positioners and micromanipulators for probe stations. (October 2018) - Hietanen, Iiro; Heikkinen, Ismo T.S.; Savin, Hele; Pearce, Joshua M.
Graphical abstract: Abstract: Three types of highly-customizable open source probe positioning systems are evaluated: (a) mostly 3-D printed, (b) partially printed using OpenBeam kinematic constraints, and (c) a 3-level stack of low-cost commercial single axis micropositioners and some printed parts. All systems use digital distributed manufacturing to enable bespoke features, which can be fabricated with RepRap-class 3-D printer and easily accessible components. They are all flexible in material choice for custom components. The micropositioners can be set up for left-right use and flat or recessed configurations using either mechanical or magnetic mounting. All systems use a manual probe holder that can be customized and enable a quick swap probe system. System (a) is purchased for $100 or fabricated for <$5, (b) fabricated for $25, and (c) fabricated for $145. Each full turn of a knob moves an axis 0.8 mm for (a) and 0.5 mm for (b, c) providing externally measured positional control of 10 µm for the latter. All three designs can utilize a customizable probe holder and tungsten carbide needle for $56. The designs are validated using microchips with known feature sizes and underwent mechanical stress tests. The maximal deflection of (a) was >200 µm, (b) 40 µm and (c) 10 µm. A tradeoff is observed for 3-D printed percent between cost and accuracy. All systems provided substantial cost savings over proprietary products with similar functionality.